Evaluation of exposure to secondhand smoke and serum level of interleukin 18 in non-smokers. (January 2022) - Azargoon, Alireza; Kharazmkia, Ali; Kordalivand, Nazanin; Birjandi, Mehdi; Mir, Samareh
Abstract: Objective: Smoking is one significant global health care problems, that not only affects the users but also endangers the health of people inhaling the smoke (passive smoking/secondhand smoke). The serum level of IL-18, an important regulator of inherent and acquired immune response, is affected by cigarette smoking. The aim of this study was to evaluate the effect of secondhand smoke (SHS) exposure on IL-18 serum level in non-smoker adults. Methods: In a case-control study, using easy sampling method, 76 non-smokers who were exposed to cigarette smoke for at least 1 h daily during the past year were considered as exposure group, while 76 of their companions without exposure to cigarette smoke (after matching age) were considered as non-exposure group. Serum IL-18 levels were measured for all participants and finally compared between the two groups using Chi-square test. P value < 0.05 was considered to be statistically significant. Results: The exposure and non-exposure groups included 58 (76.3%) and 25 (32.9%) males, respectively ( P < 0.001). The mean ± SD of age for the exposure and non-exposure groups was 35.42 ± 10.37 and 38.47 ± 12.49 years, respectively ( P = 0.102). There was no significant difference between the mean serum levels of IL-18 in the exposure (54.81 ± 57.03 ng/ml) and non-exposure (41.49 ± 42.14 ng/ml) groups ( P = 0.104). Conclusion: The exposure to secondhand smoke has no significant effect on serum level of IL-18 in exposed adult individuals. However, more studies with larger sample sizes on different populations are required to confirm these results. Highlights: Smoking is one significant global health care problems. That not only affects the users but also endangers the health of people inhaling the smoke. The serum level of IL-18, an important regulator of inherent and acquired immune response. The exposure to secondhand smoke has no significant effect on serum level of IL-18.